2002
DOI: 10.1073/pnas.072087899
|View full text |Cite
|
Sign up to set email alerts
|

Lineage infidelity in myeloid cells with TCR gene rearrangement: A latent developmental potential of proT cells revealed by ectopic cytokine receptor signaling

Abstract: The most immature lymphoid-committed progenitors in both the bone marrow (common lymphoid progenitor) and thymus (proT1) maintain a latent granulocyte͞macrophage (G͞M) differentiation potential that can be initiated by signals emanating from exogenously expressed IL-2 receptors. In this study, we investigate at which developmental stage thymocytes lose this G͞M differentiation potential. We demonstrate that the next maturational stage after proT1 cells (proT2), but not preT (TN3) cells, can convert cell fate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
103
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 44 publications
6
103
1
Order By: Relevance
“…Percentiles of EGFP þ cells are indicated; data are representative of two independent experiments. pro-T4), which could be unveiled by stimulating ectopically expressed IL-2 or GM-CSF receptors (Kondo et al, 2000;King et al, 2002;Iwasaki-Arai et al, 2003). Moreover, the macrophage differentiation of purified mouse embryonic thymocytes could be obtained in vitro with a specific combination of cytokines, provided that M-CSF was present (Lee et al, 2001), which suggested that M-CSF-R could be naturally expressed in early T progenitors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Percentiles of EGFP þ cells are indicated; data are representative of two independent experiments. pro-T4), which could be unveiled by stimulating ectopically expressed IL-2 or GM-CSF receptors (Kondo et al, 2000;King et al, 2002;Iwasaki-Arai et al, 2003). Moreover, the macrophage differentiation of purified mouse embryonic thymocytes could be obtained in vitro with a specific combination of cytokines, provided that M-CSF was present (Lee et al, 2001), which suggested that M-CSF-R could be naturally expressed in early T progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the macrophage differentiation of purified mouse embryonic thymocytes could be obtained in vitro with a specific combination of cytokines, provided that M-CSF was present (Lee et al, 2001), which suggested that M-CSF-R could be naturally expressed in early T progenitors. It has been proposed that one of the earliest event in lymphoid lineage commitment is downregulation of cytokine receptors whose normal function is to drive and support myeloid lineage differentiation (Kondo et al, 2000;King et al, 2002;Iwasaki-Arai et al, 2003). As pro-T cells are developing into lymphocytes, they gradually lose all differentiating potential into the myeloid lineage (King et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulation through ectopic cytokine receptors, such as IL-2 and GM-CSF receptors, uncovers a latent myeloid differentiation potential in CLPs and proT (DN1 and DN2) cells (9)(10)(11). Although using an artificial system, IL-2-induced lineage conversion in CLPs is a clear evidence demonstrating that cytokines can have instructive actions in determining lymphoid vs. myeloid lineage outcome (12).…”
mentioning
confidence: 99%